2016
DOI: 10.1002/celc.201600177
|View full text |Cite
|
Sign up to set email alerts
|

The Electric Double Layer in an Ionic Liquid Incorporated with Water Molecules: Atomic Force Microscopy Force Curve Study

Abstract: Electrochemical techniques and atomic force microscopy based force curve measurements under potential control are combined to investigate the effect of small amounts of water on the structure of the electric double layer of an Au(111)/1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)amide (BMPTFSA) interface. Three to five layering structures, including two charged layers, are observed at the Au(111)/BMPTFSA interface at potentials more negative than the point of zero charge. With an increase in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 55 publications
6
62
0
Order By: Relevance
“…Even small amounts of water can modify the interface structure of an ionic liquid under applied electric potential [108]. On the interface between butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) amide ([BMP][TFSA], also referred to as [Py 1,4 ][TFSI]) and Au(111), Zhong et al [109], using AFS, observed that upon a water increase from 30 ppm to 90 ppm, the stiffness of the first interface layers decreased significantly while the thickness of the layers increased. This indicates that at this low concentration, water absorbs on the surface and distorts the defined orientation of ions in the layer.…”
Section: Influence Of Watermentioning
confidence: 99%
“…Even small amounts of water can modify the interface structure of an ionic liquid under applied electric potential [108]. On the interface between butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) amide ([BMP][TFSA], also referred to as [Py 1,4 ][TFSI]) and Au(111), Zhong et al [109], using AFS, observed that upon a water increase from 30 ppm to 90 ppm, the stiffness of the first interface layers decreased significantly while the thickness of the layers increased. This indicates that at this low concentration, water absorbs on the surface and distorts the defined orientation of ions in the layer.…”
Section: Influence Of Watermentioning
confidence: 99%
“…They did not observe evidence of electrosorption of water on ions layered at the ionophilic gold electrodes. However, AFM force curves showed that the incorporated water molecules weaken the stability of layered structures 39 . Despite these modeling and experimental studies, some critical questions, regarding the electrosorption of water on electrodes, remained unanswered, such as (1) effects of the nature of electrode materials, from gold to carbon, on water electrosorption, (2) differences between hydrophobic and hydrophilic RTILs, and (3) how to prevent water adsorption on electrode surfaces to avoid electrochemical reaction.…”
Section: Introductionmentioning
confidence: 98%
“…For humid ILs, it has been found that water molecules prefer to accumulate on charged electrode surfaces 13 15 . Very unfavorable to EES devices, the surface-adsorbed water can effectively narrow the electrochemical windows of ILs due to its electrolysis, resulting in performance degradation 13 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that due to the strong interaction with anions, water molecules are excluded from the negatively charged electrode with hydrophilic ILs 18 . However, it is still an unaddressed issue that, for hydrophobic ILs that have been widely used as electrolytes 19,20 , they become humid when exposed to the atmosphere 12 , and unfortunately, their water much favors adsorption on both negatively and positively charged electrodes 15,16,18 . To avoid compromising their wide electrochemical windows, it is of great importance to minimize surface-adsorbed water and its impact, and thus enhance the voltage window of humid hydrophobic ILs.…”
mentioning
confidence: 99%